CD8+ T-cell mediated anti-malaria protection induced by malaria vaccines; assessment of hepatic CD8+ T cells by SCBC assay. Issue 7 (3rd July 2017) - Zhou, Jing; Kaiser, Alaina; Ng, Colin; Karcher, Rachel; McConnell, Tim; Paczkowski, Patrick; Fernandez, Cristina; Zhang, Min; Mackay, Sean; Tsuji, Moriya
ABSTRACT: Malaria is a severe infectious disease with relatively high mortality, thus having been a scourge of humanity. There are a few candidate malaria vaccines that have shown a protective efficacy in humans against malaria. One of the candidate human malaria vaccines, which is based on human malaria sporozoites and called PfSPZ Vaccine, has been shown to protect a significant proportion of vaccine recipients from getting malaria. PfSPZ Vaccine elicits a potent response of hepatic CD8+ T cells that are specific for malaria antigens in non-human primates. To further characterize hepatic CD8+ T cells induced by the sporozoite-based malaria vaccine in a mouse model, we have used a cutting-edge Single-cell Barcode (SCBC) assay, a recently emerged approach/method for investigating the nature of T-cells responses during infection or cancer. Using the SCBC technology, we have identified a population of hepatic CD8+ T cells that are polyfunctional at a single cell level only in a group of vaccinated mice upon malaria challenge. The cytokines/chemokines secreted by these polyfunctional CD8+ T-cell subsets include MIP-1α, RANTES, IFN-γ, and/or IL-17A, which have shown to be associated with protective T-cell responses against certain pathogens. Therefore, a successful induction of such polyfunctional hepatic CD8+ T cells may be a key to the development of effective human malaria vaccine. In addition, the SCBC technology could provide a new level of diagnostic that will allow for a more accurate determination of vaccine efficacy.